If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -12 + 4n = 4 Solving -12 + 4n = 4 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 4n = 4 + 12 Combine like terms: -12 + 12 = 0 0 + 4n = 4 + 12 4n = 4 + 12 Combine like terms: 4 + 12 = 16 4n = 16 Divide each side by '4'. n = 4 Simplifying n = 4
| -11+b=-3 | | 19a-12-4a=(-57) | | (Y6/Y3)4 | | k/18=-4 | | 393=17n+2 | | 13=11-y | | m/15=16 | | -6x-10=-16 | | -5d-24=4(1d+6)-1d | | 6x+21=6x+24-3 | | 2(2z-3)-2(4-5z)=2 | | -50x^10/10x^5 | | -5-3x=25 | | 2m-8=6 | | 3a^2+10=0 | | 5x(x-3)+6=5x-9 | | m+-1=9 | | 6x+6.32=2x+14 | | -5s-16=-4s | | -(4/x-4)=5 | | 9-5n=39 | | 16i+5=3oi-2 | | .5x+8.5-15=-3 | | 5y+5=4z+9 | | 1.33t-8=-12 | | x+17477=1345676543427 | | (7x^2-22x)/(7x-1) | | 7b+6a=69 | | 18=m/3 | | 5.19-1.54x=4x-1.735 | | 10=8-k | | -13r=260 |